Tire
By using a rubber composition with high silica content and a micro-bulge structure in the sidewall of the tire, the problem of insufficient crack resistance of the sidewall is solved, and the effect of longer life and lower environmental load is achieved.
Patent Information
- Application Number
- CN202410752491.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-07-13
- Filing Date
- 2024-06-12
- Publication Date
- 2025-01-14
AI Technical Summary
The crack resistance of the sidewalls of existing tires is insufficient, making it difficult to meet the needs of longevity, especially in terms of environmental loads.
Using a rubber composition, which contains rubber components and more than 20% silica, the loss tangent (tanδ) and complex elastic modulus (E*) of the rubber composition at 70°C meet a specific relationship and is in the sidewall Thickness and load capacity are optimized while multiple tiny bulges are formed on the outer surface of the sidewall to reduce stress concentration.
It significantly improves the crack resistance of the sidewall, extends the service life of the tire, and reduces the environmental load.
Smart Images

Figure CN119305341A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to tires. Background Art
[0002] With the increasing demand for the fuel efficiency of tires, in order to improve the fuel efficiency of tires, low fuel efficiency has been studied not only in the tread portion of the tire, but also in other parts such as the sidewall. For example, Patent Document 1 states that the fuel efficiency can be improved by using a rubber composition containing a specific resin in the sidewall of the tire. [Prior art literature] [Patent Document]
[0003] [Patent Document 1] JP Patent Publication No. 2021-14506 Summary of the invention [Problems to be solved by the invention]
[0004] On the other hand, from the perspective of reducing environmental load, etc., there is a demand for longer tire life, and there is room for improvement in terms of improving the crack resistance of the sidewall and further extending the life.
[0005] An object of the present invention is to improve the crack resistance of a sidewall. [Methods used to solve the problem]
[0006] The present invention relates to the following tire. A tire, characterized in that the tire comprises a pair of sidewalls. The rubber composition constituting the sidewall contains a rubber component and silica, wherein the content of the silica is 20 parts by mass or more relative to 100 parts by mass of the rubber component. When the loss tangent (tanδ) of the rubber composition at 70°C is 70°C tanδ, the complex elastic modulus (MPa) of the rubber composition at 70°C is 70°C E*, and the thickness (mm) of the sidewall of the tire at the maximum width position is T, 70°C tanδ, 70°C E* and T satisfy the following relationship. (1) tanδ at 70℃ < 0.0253 × T + 0.083 (2) 70℃E*≤10.0 [Effects of the Invention]
[0007] According to the present invention, it is possible to provide a tire having improved crack resistance of a sidewall. BRIEF DESCRIPTION OF THE DRAWINGS
[0008] [ Figure 1 ] is a diagram showing the tire cross-sectional width Wt, tire cross-sectional height Ht, and tire outer diameter Dt, etc. in the cross-section of the tire. [ Figure 2 ] is a schematic diagram of the outer surface of the sidewall formed with multiple columnar tiny protrusions. [ Figure 3 ] is a schematic diagram of the outer surface of the sidewall formed with multiple tetrahedral pyramid-shaped tiny protrusions. [ Figure 4 ]yes Figure 3 XX cross-section diagram. [ Figure 5 ] is a schematic diagram of the outer surface of the sidewall formed with multiple rib-like tiny protrusions. [ Figure 6 ]yes Figure 5 YY cross-section diagram. [reference numerals] Wt: tire section width Ht: Tire section height Dt: tire outer diameter T: Thickness of the sidewall PW: Maximum tire width position L: Normal 1: External surface of the sidewall 2: Small bulge 3: Small bulge 4: Small bulge w: Maximum width of the tiny bump d: Interval between tiny bumps h: height of the tiny bump. DETAILED DESCRIPTION
[0009] The present invention relates to the following tire. A tire, characterized in that the tire comprises a pair of sidewalls. The rubber composition constituting the sidewall contains a rubber component and silica, wherein the content of the silica is 20 parts by mass or more relative to 100 parts by mass of the rubber component. When the loss tangent (tanδ) of the rubber composition at 70°C is 70°C tanδ, the complex elastic modulus (MPa) of the rubber composition at 70°C is 70°C E*, and the thickness (mm) of the sidewall of the tire at the maximum width position is T, 70°C tanδ, 70°C E* and T satisfy the following relationship. (1) tanδ at 70℃ < 0.0253 × T + 0.083 (2) 70℃E*≤10.0
[0010] Although not intended to be bound by theory, it is believed that in the present invention, the mechanism that can improve the crack resistance of the sidewall is as follows. That is, first, (1) since the sidewall deforms during rolling, cracks are easily generated due to the accumulation of deformation. Therefore, the complex elastic modulus of the sidewall rubber is set to a specified value or less to make it soft. Accordingly, it is possible to deform softly for the strain generated on the surface, so the generation of cracks can be suppressed. In addition, (2) the higher the loss tangent tanδ of the sidewall rubber, the higher the temperature rises due to the deformation during rolling, the lower the fracture characteristics are, and cracks are easily generated. Therefore, according to the thickness of the sidewall rubber, the tanδ is reduced. Accordingly, when the thickness of the sidewall rubber is thick, the deformation is suppressed by ensuring the rigidity of the sidewall, and when the thickness of the sidewall rubber is thin, the heat generated by the deformation is suppressed, and the temperature rise in the sidewall is easily suppressed, so the state of high fracture characteristics can be maintained. In addition, (3) silica as a filler is more difficult to bind the surrounding polymer than carbon black. Therefore, by adding a predetermined amount or more of silica, the elongation at break is increased, the flexibility of the rubber is increased, and the generation of cracks can be suppressed. Furthermore, the above (1) to (3) work together to achieve high crack resistance.
[0011] Preferably, the rubber composition contains carbon black, and the content (mass parts) of the silica is A to B relative to 100 parts by mass of the rubber component. SIL The content of carbon black (parts by mass) is A CB When A SIL and A CB The following relationship is satisfied. (3)A CB / A SIL ≤1
[0012] By blending a large amount of silica as a filler, the silica can contribute to the improvement of crack resistance by utilizing the advantage of being less likely to bind surrounding polymers than carbon black.
[0013] Preferably, the rubber composition comprises carbon black, and the carbon black comprises recovered carbon black (rCB).
[0014] Since the surface of rCB is incinerated, the bonding with the surrounding rubber molecules tends to be slightly weaker. Therefore, it is believed that the surrounding rubber molecular chains are more likely to release force when deformed, which helps to improve the crack resistance of the sidewall.
[0015] Preferably, the silicon dioxide contains silicon dioxide having an average primary particle size of 16 nm or less.
[0016] By adding silica having a smaller particle size, heat generation due to friction between silica particles can be reduced, a temperature rise of the sidewall can be suppressed, and a state of excellent fracture characteristics can be maintained, thereby improving crack resistance.
[0017] Preferably, when the tire weight (kg) of the tire is G and the maximum load capacity (kg) is WL, G and WL satisfy the following relationship. (4)G / WL≤0.0180
[0018] The maximum load capacity of a tire is a value proportional to the virtual volume of the tire. Therefore, it is believed that by increasing the maximum load capacity relative to the tire weight, the thickness of the tire as a whole becomes thinner, which can improve the heat dissipation effect and thus contribute to the improvement of crack resistance.
[0019] Preferably, at least one of the pair of sidewalls has a micro-ridge forming portion having a plurality of micro-ridges formed on an outer surface thereof.
[0020] The provision of the micro-protrusion forming portion can suppress stress concentration on the outer surface of the sidewall, thereby contributing to improvement of the crack resistance of the sidewall.
[0021] Preferably, the micro-protrusions are in the shape of columns, cones or ribs.
[0022] By setting the shape of the micro-protrusions to these predetermined shapes, stress concentration on the outer surface of the sidewall can be suppressed, thereby contributing to improvement of the crack resistance of the sidewall.
[0023] Preferably, the height of the micro-ridges is greater than or equal to 0.03 mm and less than or equal to 0.50 mm, more than 20 micro-ridges are formed at intervals of less than 0.50 mm in at least one direction, and the micro-ridge forming portion has a 10 mm 2 The area above.
[0024] By setting the size of the micro-ridges within these predetermined ranges, stress concentration on the outer surface of the sidewall can be suppressed, thereby contributing to improvement of the crack resistance of the sidewall.
[0025] Preferably, the maximum width of the micro-protrusions is greater than or equal to 0.03 mm and less than or equal to 5.0 mm.
[0026] By setting the maximum width of the micro-ridges within a predetermined range, stress concentration on the outer surface of the sidewall can be suppressed, thereby contributing to improvement of the crack resistance of the sidewall.
[0027] Preferably, the height of the micro-ridges gradually increases from the maximum width position of the tire toward the outer side in the tire radial direction, and gradually increases from the maximum width position of the tire toward the inner side in the tire radial direction.
[0028] Although relatively large strain is generated near the maximum width position of the tire on the sidewall, the height of the tiny ridges is made lower as they are closer to the maximum width position of the tire. This reduces the unevenness of the rubber volume in the circumferential direction of the tire at the position where large strain is generated, avoids stress concentration near the tiny ridges, and helps improve the crack resistance of the sidewall.
[0029] <Definition> The "normal state" is an unloaded state in which the rim is assembled on a normal rim and filled with a normal internal pressure. Unless otherwise specified, the "dimensions of each part of the tire" are values specified in the normal state.
[0030] "Regular rims" are rims specified for each tire in a specification system that includes the specifications on which the tire is based. For example, in JATMA (Japan Motor Vehicle Tire Association), it refers to the standard rims in the applicable sizes listed in the "JATMA Yearbook", in ETRTO (The European Tyre and Rim Technical Organisation), it refers to the "Measuring Rim" listed in the "Standards Manual", and in TRA (The Tire and Rim Association, Inc.), it refers to the "Design Rim" listed in the "Yearbook". Reference is made to JATMA, ETRTO, and TRA in that order. If there are applicable sizes when referring, then that specification shall be followed. Furthermore, in the case of tires not specified in the specifications, it refers to a rim that can be assembled on a rim and maintain internal pressure, that is, a rim that does not cause air leakage between the rim and the tire, and has the smallest rim diameter and the narrowest rim width.
[0031] "Normal internal pressure" refers to the air pressure specified for each tire in each specification system including the specifications on which the tire is based. In JATMA, it refers to the "maximum air pressure", in ETRTO, it refers to the "inflation pressure (INFLATIONPRESSURE)", and in TRA, it refers to the maximum value recorded in the table "Tire load limits at various cold inflation pressures (TIRELOADLIMITS AT VARIOUS COLD INFLATION PRESSURES)". Similar to regular rims, reference is made in the order of JATMA, ETRTO, and TRA. If there is an applicable size when referencing, then the specification is followed. In addition, in the case of tires not specified in the specifications, it refers to the normal internal pressure (of which 250 kPa or more) of other tire sizes (tire sizes specified in the specifications) recorded with the regular rim as the standard rim. It should be noted that in the case of multiple normal internal pressures of 250 kPa or more, it refers to the minimum value among them.
[0032] “Tire weight (G) (kg)” is the weight of the tire itself excluding the weight of the rim. In addition, when a sound-absorbing material, a sealing material, a sensor, etc. are installed in the inner cavity of the tire, G is a value including their weight.
[0033] "Maximum load capacity (WL) (kg)" is the value calculated by the following formula (A) and formula (B) when the tire cross-section width is Wt (mm), the tire cross-section height is Ht (mm), and the tire outer diameter is DT (mm) measured under normal conditions. V is the imaginary volume of the space occupied by the tire. The tire cross-section width Wt is the maximum width between the outer surfaces of the sidewalls excluding patterns or texts, etc., when there are patterns or texts, etc. on the side of the tire under normal conditions. The tire cross-section height Ht is the distance from the bottom surface of the bead portion to the outermost surface of the tread, which is 1 / 2 of the difference between the outer diameter Dt of the tire and the rim diameter R (mm). V = {(Dt / 2) 2 -(Dt / 2-Ht) 2}×π×Wt···(A) WL=0.000011×V+100···(B)
[0034] "Thickness (T) (mm) of the sidewall" refers to the thickness (mm) of the rubber constituting the sidewall measured along the normal line L of the tire maximum width position PW of the sidewall. "Tire maximum width position PW" refers to the position on the sidewall surface where the tire cross-sectional width Wt is measured. T is measured when the tire cut by a plane passing through the tire rotation axis is placed on a regular rim.
[0035] The "micro protrusion" refers to a convex protrusion formed on the outer surface of the sidewall and having a height of 0.03 mm to 5.0 mm. Preferably, the maximum width of the micro protrusion is 0.03 mm to 5.0 mm.
[0036] The "micro-ridge formed portion" refers to a portion on the outer surface of the sidewall where the micro-ridge is formed.
[0037] "Regenerated carbon black" is carbon black obtained from the thermal decomposition process of used tires and other products containing carbon black, and refers to carbon black whose mass ratio of the unburned component, i.e., ash content (ash content), is 13% by mass or more when heated in air for oxidative combustion by thermogravimetric determination based on JIS K 6226-2:2003. That is, the mass of the reduced component (carbon content) caused by the oxidative combustion is 87% by mass or less. Regenerated carbon black is also represented by rCB.
[0038] The "content of plasticizer" also includes the amount of plasticizer in the rubber component filled with the plasticizer. Similarly, the "content of oil" also includes the amount of oil contained in the oil-extended rubber.
[0039] <Measurement method> Styrene content 1 H-NMR measurement and calculation.
[0040] The "vinyl bond amount (1,2-bonded butadiene unit amount)" is measured by infrared absorption spectroscopic analysis.
[0041] The “cis content (amount of cis-1,4-bonded butadiene units)” is measured by infrared absorption spectroscopic analysis.
[0042] The “weight average molecular weight (Mw)” can be determined by conversion to standard polystyrene based on the value measured by gel permeation chromatography (GPC) (GPC-8000 series manufactured by Tosoh Corporation, detector: differential refractometer, column: TSKGELSUPERMULTIPOREHZ-M manufactured by Tosoh Corporation).
[0043] “N2SA of carbon black” is a value determined according to JIS K 6217-2:2017.
[0044] "N2SA of silica" is a value measured by the BET method according to ASTM D3037-93.
[0045] The "average primary particle size" is obtained by taking a photograph of particles with a transmission or scanning electron microscope and calculating the arithmetic average of 400 particle sizes. Regarding the particle size, when the shape of the particles is roughly circular, the diameter of the circle is used as the particle size, and when the shape of the particles is needle-shaped or rod-shaped, the short diameter is used as the particle size. In other cases, the equivalent circle diameter is calculated from the electron microscope image and used as the particle size. The equivalent circle diameter is calculated as the positive square root of "4×(area of the particle) / π". The average primary particle size is applicable to silica or carbon black, etc.
[0046] Unless otherwise specified, the softening point of a resin or the like is the softening point specified in JIS K 6220-1:2015 and is the temperature at which the ball falls, as measured by a ring and ball softening point measuring apparatus. The softening point measured by other methods will be described in detail.
[0047] "70°C tanδ" is measured using the EPLEXOR series manufactured by GABO under the conditions of temperature 70°C, initial strain 10%, dynamic strain ±1%, frequency 10 Hz, and elongation mode. When collecting samples from tires, samples of 20 mm in length × 4 mm in width × 1 mm in thickness are collected from the rubber layer inside the sidewall of each test tire, so that the tangent direction of the tire circumference becomes the long side and the tire width direction becomes the thickness.
[0048] "70℃E*" is the complex elastic modulus (MPa) measured using the EPLEXOR series manufactured by GABO under the conditions of temperature 70℃, initial strain 10%, dynamic strain ±1%, frequency 10 Hz, and elongation mode. When sampling from a tire, it is the same as the case of 70℃ tanδ.
[0049] <Tires> Hereinafter, the tire of the present invention will be described with reference to the accompanying drawings as appropriate. Figure 1 However, the drawings are only examples for explanation.
[0050] The tire of the present invention is a tire as follows: the rubber composition constituting the sidewall contains 20 parts by mass or more of silica relative to 100 parts by mass of the rubber component, and the 70°C tanδ and 70°C E* (MPa) of the rubber composition, and the thickness T (mm) of the sidewall of the tire at the maximum width position satisfy the prescribed relationship represented by the above formula (1) and the above formula (2).
[0051] Figure 1 It is a cross-sectional view of a tire having a pair of sidewalls, taken along a plane passing through the tire rotation axis. Figure 1 In the figure, Wt represents the tire section width, Ht represents the tire section height, and Dt represents the tire outer diameter. Figure 1As shown, the thickness T of the sidewall is the thickness of the rubber constituting the sidewall measured along the normal line L of the tire maximum width position PW of the sidewall. Here, the tire maximum width position PW refers to the position on the outer surface of the sidewall where the tire cross-sectional width Wt is measured.
[0052] (Formula (1)) The relationship satisfied by formula (1) is as follows. (1) tanδ at 70℃ < 0.0253 × T + 0.083
[0053] In formula (1), the difference obtained by subtracting the value on the left from the value on the right is preferably greater than 0.010, more preferably greater than 0.020, further preferably greater than 0.030, further preferably greater than 0.040, further preferably greater than 0.050, further preferably greater than 0.060, further preferably greater than 0.070.
[0054] The tanδ at 70°C is preferably less than 0.130, more preferably less than 0.120, further preferably less than 0.115, further preferably 0.112 or less, further preferably less than 0.110. The lower limit of the tanδ at 70°C is not particularly limited from the perspective of the effect of the invention, and is, for example, preferably 0.020 or more, more preferably 0.030 or more, further preferably 0.050 or more.
[0055] The 70°C tanδ of the rubber composition can be appropriately adjusted according to the type or compounding amount of the components constituting the rubber composition described below. For example, by increasing the amount of filler, reducing its particle size, reducing the amount of vulcanizing agent and vulcanization accelerator, etc., there is a tendency to increase the 70°C tanδ. Therefore, by the opposite operation, there is a tendency to reduce the 70°C tanδ.
[0056] The thickness T (mm) of the sidewall is not particularly limited as long as it is within the range of thickness that can be generally adopted. For example, in the case of a tire for a passenger car, T is preferably greater than 1.0 mm, more preferably greater than 1.5 mm, and further preferably greater than 2.0 mm. On the other hand, T is preferably less than 10.0 mm, more preferably less than 9.0 mm, further preferably less than 8.0 mm, further preferably less than 7.0 mm, and further preferably less than 6.0 mm.
[0057] (Formula (2)) The relationship satisfied by formula (2) is as follows. (2) 70℃E*≤10.0
[0058] The value on the right side of formula (2) is preferably 8.0, more preferably 6.0, further preferably 5.0, further preferably 4.7, further preferably 4.1, further preferably 4.0, further preferably 3.6. The lower limit of the value of 70°C E* is not particularly limited from the perspective of the effect of the present invention, and may be, for example, 2.0 or 3.0.
[0059] The 70°C E* of the rubber composition can be appropriately adjusted according to the types or compounding amounts of the components constituting the rubber composition described below. For example, by increasing the amount of filler, reducing its particle size, reducing the total amount of plasticizer, and increasing the amount of vulcanizer and vulcanization accelerator, there is a tendency to increase the 70°C E*. Therefore, by the opposite operation, there is a tendency to reduce the 70°C E*.
[0060] (Formula (3)) The relationship satisfied by the formula (3) is as follows. This point will be described in the explanation of the filler. (3)A CB / A SIL ≤1
[0061] (Formula (4)) The relationship satisfied by formula (4) is as follows. (4)G / WL≤0.0180
[0062] The tire of the present invention that satisfies the above formula (4) is a tire with a large maximum load capacity relative to the tire weight. The right side of formula (4) is preferably 0.0170, more preferably 0.0165, and further preferably 0.0161. On the other hand, the lower limit of G / WL is not particularly limited from the perspective of the effect of the present invention, and as a reference value, for example, is about 0.0120.
[0063] The value of G / WL can be decreased by reducing the relative value of G with respect to the value of WL, and conversely, can be increased by increasing the relative value of G with respect to the value of WL.
[0064] As described above, WL is a value determined based on the tire cross-sectional width Wt (mm), the tire cross-sectional height Ht (mm), and the tire outer diameter Dt (mm). Figure 1 The Wt, Ht and Dt of the tire are shown.
[0065] (Micro-ridge formation area) Preferably, the tire of the present invention has a micro-ridge forming portion in which a plurality of micro-ridges are formed on an outer surface of at least one of the pair of sidewalls.
[0066] In the micro-protrusion forming portion, the micro-protrusions may be arranged in one row or in multiple rows in the tire radial direction. Here, being in one row in the tire radial direction means that there are not more than two micro-protrusions arranged in the tire radial direction. In addition, the micro-protrusions may be arranged in one row or in multiple rows in the tire circumferential direction. Here, being in one row in the tire circumferential direction means that there are not more than two micro-protrusions arranged in the tire circumferential direction. Preferably, the micro-protrusions are arranged in multiple rows in the tire radial direction and in multiple rows in the tire circumferential direction.
[0067] The area of the micro-ridge formation portion refers to the area defined by a line enclosing the outermost portion of a plurality of micro-ridges arranged at intervals of 0.50 mm or less when viewed in a direction perpendicular to the tire surface. The area of the micro-ridge formation portion is preferably 10 mm 2 This is because it can suppress stress concentration on the outer surface of the sidewall, which helps to improve the crack resistance of the sidewall. In addition, in the micro-protrusion forming portion, the collection formed by the micro-protrusions can be continuous or disjoint. Here, disjoint means that the interval between the micro-protrusions is greater than 1.0 mm. Therefore, the micro-protrusion forming portion only needs to exist on the outer surface of at least one of the pair of sidewalls, or it can exist in multiple forms.
[0068] (Slight bulge) The shape of the micro-protrusion is not particularly limited as long as it helps to suppress stress concentration on the outer surface of the sidewall and improve the crack resistance of the sidewall. Specifically, columnar, truncated cone, rib (rib) and the like can be cited. As a columnar shape, in addition to a cylindrical shape, it also includes a triangular prism, a square prism, a pentagonal prism and other polygonal prisms. As a truncated cone shape, in addition to a circular truncated cone shape, it also includes a triangular truncated cone, a square truncated cone, a pentagonal truncated cone and other polygonal truncated cones. As a rib, there is no particular limitation on the shape of the cross section of the rib-shaped micro-protrusion perpendicular to the length direction, and it can include any shape. As the shape of the cross section, for example, a rectangle or a trapezoid can be cited.
[0069] Figure 2 A part of a micro-protrusion forming portion in which cylindrical micro-protrusions 2 are formed on the sidewall outer surface 1 is shown. Figure 3 A part of a micro-protrusion forming portion in which quadrangular pyramid-shaped micro-protrusions 3 are formed on the sidewall outer surface 1 is shown. Figure 4 yes Figure 3 The XX cross-sectional view is a view of the micro-ridge observed from a direction perpendicular to a plane including a normal line erected on the outer surface of the tire sidewall. Figure 4 The height h of the micro-ridges 3 , the maximum width w of the micro-ridges 3 , and the interval d between the micro-ridges 3 are shown. Figure 5 A part of a micro-protrusion forming portion where rib-shaped micro-protrusions 4 are formed on the sidewall outer surface 1 is shown. Figure 6 yes Figure 5The YY cross-sectional view is a view of the micro-ridge observed from a direction perpendicular to a plane including a normal line erected on the outer surface of the tire sidewall. Figure 6 The height h of the micro-ridges 4 , the maximum width w of the micro-ridges 4 , and the interval d between the micro-ridges 4 are shown.
[0070] Here, for a micro-protrusion, "height" refers to the maximum height of the micro-protrusion measured along the normal line erected on the outer surface of the tire sidewall, "maximum width" refers to the maximum width of the micro-protrusion on the outer surface of the tire sidewall measured in one direction in which the micro-protrusions are arranged, and "interval" refers to the minimum interval of the micro-protrusions on the outer surface of the tire sidewall measured in one direction in which the micro-protrusions are arranged. It should be noted that the height, maximum width and interval of the micro-protrusions are all measured when the outer surface of the tire sidewall is unfolded onto a plane.
[0071] The height of the micro-ridges at the maximum width position of the tire is preferably 0.03 mm or more, may be 0.05 mm or more, or may be 0.10 mm or more. On the other hand, the height is preferably 0.50 mm or less, may be 0.45 mm or less, or may be 0.40 mm or less. In addition, the maximum width of the micro-ridges is preferably 0.03 mm or more, may be 0.05 mm or more, or may be 0.10 mm or more. On the other hand, the maximum width is preferably 5.00 mm or less, may be 3.00 mm or less, or may be 1.00 mm or less, or may be 0.50 mm or less. In addition, the interval between the micro-ridges is preferably 1.00 mm or less, may be 0.70 mm or less, or may be 0.50 mm or less. It should be noted that the interval between the micro-ridges only needs to be at least about half of the maximum width, and may be the same as the maximum width. It should be noted that the density of the micro-ridges (number / cm 2 ) can be estimated based on the maximum width and spacing of the micro-ridges. For example, in the case of the embodiment described below, it is about 700 / cm 2 .
[0072] Preferably, 20 or more micro-ridges are formed in at least one direction. This is because stress concentration on the outer surface of the sidewall can be suppressed, which helps improve the crack resistance of the sidewall.
[0073] Preferably, the height of the micro-bulge gradually increases from the maximum width position of the tire to the outer side of the tire radial direction, and gradually increases from the maximum width position of the tire to the inner side of the tire radial direction. This is because, although a relatively large strain is generated near the maximum width position of the tire sidewall, by making the height of the micro-bulge lower as it is closer to the maximum width position of the tire, the unevenness of the rubber volume in the tire circumferential direction at the position where a large strain is generated can be reduced, and stress concentration near the micro-bulge can be avoided, which helps to improve the crack resistance of the sidewall.
[0074] Preferably, the micro-protrusions are Figure 5 As shown in the micro-protrusion 4 shown in FIG, there is an arc-shaped concave portion on the outermost surface of the micro-protrusion. This is because, by setting it as such a structure, air can be suppressed from being trapped in the arc-shaped concave portion, thereby suppressing the occurrence of poor appearance of the micro-protrusion.
[0075] <Rubber Composition> The rubber composition constituting the sidewall of the tire of the present invention is described below. The rubber composition contains a rubber component and silica, wherein the content of the silica is 20 parts by mass or more per 100 parts by mass of the rubber component, and may further contain other compounding ingredients.
[0076] (Rubber component) Preferably, the rubber component contains at least one diene rubber component selected from isoprene rubber (IR rubber), styrene butadiene rubber (SBR) and butadiene rubber (BR). In addition, the rubber component may contain at least two rubber components selected from IR rubber, SBR and BR, or may contain IR rubber, SBR and BR. Among them, the rubber component preferably contains IR rubber and BR, and may be composed only of IR rubber and BR. In addition, these rubber components may be filled rubbers filled with plasticizers described later, or may be rubber components subjected to modification treatment or hydrogenation treatment in which hydrogen is added to double bonds.
[0077] 《Isoprene rubber》 As isoprene-based rubber, natural rubber (NR), isoprene rubber (IR), modified NR, modified NR, modified IR, etc. can be mentioned. As NR, for example, NR commonly used in the tire industry such as SIR20, RSS#3, TSR20, etc. can be used. As IR, there is no particular limitation, for example, IR commonly used in the tire industry such as IR2200 can be used. As modified NR, deproteinized natural rubber (DPNR), high purity natural rubber (UPNR), etc. can be mentioned; as modified NR, epoxidized natural rubber (ENR), hydrogenated natural rubber (HNR), grafted natural rubber, etc. can be mentioned; as modified IR, epoxidized isoprene rubber, hydrogenated isoprene rubber, grafted isoprene rubber, etc. can be mentioned. They can be used alone, or two or more kinds can be used in combination.
[0078] From the viewpoint of improving the elongation at break of the rubber composition and improving the crack resistance, the content of the isoprene-based rubber in 100% by mass of the rubber component is preferably greater than 20% by mass, more preferably greater than 30% by mass, further preferably greater than 40% by mass, and further preferably 45% by mass or more. On the other hand, from the viewpoint of suppressing deterioration due to heat or the like, the content is preferably less than 75% by mass, more preferably less than 65% by mass, and further preferably less than 55% by mass.
[0079] 《SBR》 As SBR, there is no particular limitation, for example, emulsion polymerization styrene butadiene rubber (E-SBR), solution polymerization styrene butadiene rubber (S-SBR) etc. can be used. In addition, SBR can be non-modified SBR, or can be modified SBR. In addition, as SBR, hydrogenated styrene-butadiene copolymer (hydrogenated SBR) can also be used. They can be used alone, or two or more can be used in combination.
[0080] The styrene content of SBR is preferably greater than 5.0% by mass, more preferably greater than 7.5% by mass, and further preferably greater than 10.0% by mass. The styrene content is preferably less than 40.0% by mass, more preferably less than 35.0% by mass, and further preferably less than 30.0% by mass. By setting it within the above range, a microscopic styrene domain can be formed in the rubber component, which can easily absorb the strain caused by deformation in the rubber composition. It should be noted that in this specification, the styrene content can be expressed by 1 The results were determined by H-NMR measurement.
[0081] The vinyl bond content of SBR is preferably greater than 5 mol%, more preferably greater than 10 mol%, and further preferably greater than 15 mol%. The vinyl bond content is preferably less than 65 mol%, more preferably less than 60 mol%, and further preferably less than 50 mol%. It should be noted that the vinyl bond content can be measured by the above method.
[0082] As SBR, SBR filled with a plasticizer (filled SBR) can be used, or non-filled SBR can be used. When using filled SBR, the amount of SBR filled, i.e., the content of the filled plasticizer contained in SBR is preferably 10 to 50 parts by mass relative to 100 parts by mass of the rubber solid component of SBR. As the plasticizer used for filling, resins, oils, liquid polymers, ester plasticizers, etc. described later can be cited.
[0083] As the SBR, for example, SBR manufactured and sold by Sumitomo Chemical Co., Ltd., JSR Corporation, Asahi Kasei Corporation, Nippon Zeon Corporation, etc. can be used.
[0084] In 100% by mass of the rubber component, the content of SBR may be 0% by mass, but, for example, may be greater than 1% by mass, greater than 5% by mass, or greater than 10% by mass. The upper limit of the content of SBR is preferably less than 40% by mass, more preferably less than 35% by mass, and further preferably less than 30% by mass.
[0085] 《BR》 BR is not particularly limited, and for example, high cis BR having a high cis content, BR containing syndiotactic polybutadiene crystals, BR synthesized using a rare earth catalyst (rare earth BR), etc. can be used. These can be used alone or in combination of two or more.
[0086] Among them, BR preferably contains high cis BR having a cis content of more than 90% by mass. The cis content is more preferably more than 95% by mass, and more preferably 98% by mass or more. It should be noted that the cis content can be measured by the above method.
[0087] In addition, BR may be unmodified BR or modified BR. As modified BR, there can be mentioned modified BR into which the same functional group as that of the modified diene rubber is introduced. In addition, as BR, a hydrogenated butadiene polymer (hydrogenated BR) may be used.
[0088] As BR, for example, products of Ube Industries, Ltd., JSR Corporation, Asahi Kabushiki Kaisha, Nippon Zeon Corporation, etc. can be used.
[0089] From the perspective of low fuel consumption and crack growth resistance, the BR content in 100% by mass of the rubber component is preferably greater than 20% by mass, more preferably greater than 25% by mass, further preferably greater than 30% by mass, further preferably greater than 35% by mass, further preferably greater than 40% by mass. Further preferably greater than 45% by mass, further preferably greater than 50% by mass, further preferably greater than 55% by mass. On the other hand, as an upper limit, it is preferably less than 75% by mass, more preferably less than 70% by mass, further preferably less than 65% by mass.
[0090] 《Other rubber ingredients》 As the rubber component, rubbers other than the above can be used. As rubbers other than the above, diene rubbers such as styrene isoprene butadiene rubber (SIBR), chloroprene rubber (CR), acrylonitrile butadiene rubber (NBR), and non-diene rubbers such as ethylene propylene diene rubber (EPDM), butyl rubber (IIR), and halogenated butyl rubber (X-IIR) can be cited. These can be used alone or in combination of two or more.
[0091] The content of the diene rubber in 100% by mass of the rubber component is preferably more than 80% by mass, more preferably more than 90% by mass, and most preferably 100% by mass.
[0092] (Bulking Agent) The rubber composition constituting the sidewall of the present invention contains 20 parts by mass or more of silica relative to 100 parts by mass of the rubber component. The silica preferably contains a nitrogen adsorption specific surface area (N2SA) of 180 m 2 / g or more of silicon dioxide can be obtained by N2SA of 180m 2 The rubber composition constituting the sidewall of the present invention preferably contains carbon black (CB), and the carbon black preferably contains regenerated carbon black (rCB).
[0093] Silicon Dioxide As silicon dioxide, dry silicon dioxide (anhydrous silicon dioxide), wet silicon dioxide (hydrous silicon dioxide) and the like can be used. Among them, wet silicon dioxide is preferred because of the large number of silanol groups. As commercially available products, products of Degussa, Rhodia, Tosoh Silica Corporation, Solvay Japan Co., Ltd., Tokuyama Corporation and the like can be used. They can be used alone, or two or more can be used in combination. In addition, in addition to these silicon dioxides, silicon dioxide made from biomass materials such as rice husks can also be used.
[0094] The nitrogen adsorption specific surface area (N2SA) of silicon dioxide is preferably greater than 50 m 2 / g, more preferably greater than 100m 2 / g, more preferably greater than 150m 2 / g, more preferably 175m 2 / g or more, more preferably 180m 2 / g or more, more preferably more than 190m 2 / g, more preferably greater than 200m2 / g, more preferably greater than 210m 2 / g, more preferably greater than 220m 2 / g, more preferably greater than 230m 2 / g, more preferably 235m 2 The upper limit of N2SA of silica is not particularly limited, but is preferably less than 600 m 2 / g, more preferably less than 350m 2 / g, more preferably less than 300m 2 / g. By setting it within the above range, there is a tendency to improve the crack growth resistance. It should be noted that the N2SA of silica is a value measured by the above method.
[0095] From the perspective of reinforcement, low fuel consumption, etc., the average primary particle size of silicon dioxide is preferably less than 25nm, more preferably less than 22nm, further preferably less than 20nm, further preferably less than 18nm, further preferably less than 17nm, further preferably less than 16nm, further preferably less than 16nm, further preferably less than 15nm. The lower limit of the average primary particle size is not particularly limited, preferably greater than 3nm, more preferably greater than 5nm, and further preferably greater than 10nm. It should be noted that the average primary particle size of silicon dioxide can be obtained by the above method.
[0096] Carbon Black (CB) As carbon black, there is no particular limitation, and any carbon black that can be used in the tire industry can be used. As such carbon black, for example, N134, N110, N220, N234, N219, N339, N330, N326, N351, N550, N660, N762, etc. can be cited. As commercial products, products of Asahi Carbon Co., Ltd., Cabot Japan Co., Ltd., Tokai Carbon Co., Ltd., Mitsubishi Chemical Corporation, Lion Corporation, Shin Nichia Carbon Co., Ltd., Columbia Carbon Co., Ltd., etc. can be used. In addition, from the perspective of environmental load, and from the perspective of reducing the friction between the carbon black surface and the rubber molecular chain and suppressing the heat generation, regenerated carbon black (rCB) obtained by thermal decomposition of used tires can be used. They can be used alone, or two or more can be used in combination.
[0097] Recycled carbon black can be obtained from the thermal decomposition process of used pneumatic tires. For example, in the specification of European Patent Application Publication No. 3427975, "Rubber Chemistry and Technology", Vol. 85, No. 3, pp. 408-449 (2012), especially pp. 438, 440, 442, it is mentioned that it can be obtained by thermal decomposition of organic materials at 550-800° C. after excluding oxygen, or by vacuum thermal decomposition at a relatively low temperature (paragraph
[0027] ). As mentioned in paragraph
[0004] of JP Patent No. 6856781, the carbon black obtained by such a thermal decomposition process generally lacks functional groups on its surface (Comparison of the surface morphology and chemistry of thermally decomposed carbon black and commercially available carbon black, Powder Technology 160 (2005) 190-193).
[0098] The regenerated carbon black preferably lacks functional groups on its surface, but it may also contain functional groups on its surface as long as it does not affect the effect of the present invention. In addition, it can be treated to contain functional groups on its surface. The treatment in a manner that the surface of the regenerated carbon black contains functional groups can be implemented by conventional methods. For example, in the specification of European Patent Application Publication No. 3173251, the carbon black obtained by the thermal decomposition process is treated with potassium permanganate under acidic conditions to obtain carbon black containing hydroxyl and / or carboxyl groups on its surface. In addition, in JP Patent No. 6856781, the carbon black obtained from the thermal decomposition process is treated with an amino acid compound containing at least one thiol group or disulfide group to obtain a carbon black whose surface is activated. The regenerated carbon black involved in this embodiment also includes carbon black treated in a manner that these surfaces contain functional groups.
[0099] As the regenerated carbon black, commercially available products such as Strable Green Carbon and LD Carbon can be used.
[0100] The average primary particle size of carbon black is preferably greater than 20nm, more preferably greater than 25nm, further preferably greater than 30nm, and particularly preferably greater than 35nm. By setting the average primary particle size of carbon black within the above range, the rubber molecules bound by the carbon black are suppressed to a minimum and become easy to move softly. Therefore, when subjected to force, even polymer molecular chains can relax stress and suppress the generation of cracks. On the other hand, from the perspective of obtaining reinforcement, the average primary particle size is preferably less than 90nm, more preferably less than 85nm, and further preferably less than 80nm. It should be noted that the average primary particle size of carbon black is measured by the above-mentioned measurement method.
[0101] From the perspective of the effect of the present invention, the nitrogen adsorption specific surface area (N2SA) of carbon black is preferably less than 90 m2 / g, more preferably less than 80m 2 / g, more preferably less than 70m 2 / g, particularly preferably less than 60m 2 / g. In addition, the N2SA is preferably greater than 10m 2 / g, more preferably greater than 20m 2 / g, more preferably greater than 30m 2 / g, more preferably 35m 2 It should be noted that the N2SA of carbon black is measured by the above-mentioned measurement method.
[0102] 《Other filling materials》 The rubber composition constituting the sidewall of the present invention may contain other fillers in addition to silica and carbon black. Such other fillers are not particularly limited, and materials known in the rubber field can be used, for example, inorganic fillers such as calcium carbonate, talc, alumina, clay, aluminum hydroxide, aluminum oxide, and mica can be cited.
[0103] Content of fillers The content of silica (total amount of silica) is 20 parts by mass or more, more preferably greater than 23 parts by mass, further preferably greater than 26 parts by mass, further preferably greater than 29 parts by mass, relative to 100 parts by mass of the rubber component. On the other hand, the content is preferably less than 60 parts by mass, more preferably less than 50 parts by mass, further preferably less than 40 parts by mass. By setting it within the above range, the rubber is appropriately reinforced, the silica surfaces become easy to slide against each other, the elongation at break (EB) is increased, and the crack resistance can be easily improved.
[0104] When carbon black is contained, the content of carbon black is preferably greater than 1 part by mass, more preferably greater than 5 parts by mass, and further preferably greater than 10 parts by mass, relative to 100 parts by mass of the rubber component, from the perspective of obtaining reinforcement and preventing degradation caused by ultraviolet rays. In addition, from the perspective of obtaining flexibility and relieving stress, the content is preferably less than 90 parts by mass, more preferably less than 80 parts by mass, further preferably less than 70 parts by mass, further preferably less than 60 parts by mass, further preferably less than 40 parts by mass, and further preferably less than 30 parts by mass.
[0105] From the perspective of the effect of the present invention, the content of the filler (the total content of the filler) is preferably greater than 20 parts by mass, more preferably greater than 30 parts by mass, and more preferably 40 parts by mass or more, relative to 100 parts by mass of the rubber component. The upper limit of the content is preferably less than 200 parts by mass, more preferably less than 150 parts by mass, and more preferably less than 100 parts by mass, for example, less than 50 parts by mass.
[0106] 《Formula (3)》 When the rubber composition constituting the sidewall of the present invention contains carbon black, the content (parts by mass) of silica relative to 100 parts by mass of the rubber component is A SIL and carbon black content (mass parts) A CB It is preferable that the following relationship is satisfied. (3)A CB / A SIL ≤1
[0107] The value of the right side of formula (3) is preferably 0.90, more preferably 0.80, further preferably 0.70, further preferably 0.60, further preferably 0.50. CB / A SIL The lower limit value of may be 0.00, or may be 0.10, or may be 0.20.
[0108] 《Silane coupling agent》 Usually, when silica is used, a silane coupling agent can be used together, but in the present invention, silica can be used without substantially containing a silane coupling agent. Here, "substantially containing" means that even if it is contained, it is contained only within a range that does not affect the effect of the present invention. The silane coupling agent is not particularly limited, and examples thereof include sulfide-based silane coupling agents such as bis(3-triethoxysilylpropyl)disulfide and bis(3-triethoxysilylpropyl)tetrasulfide; mercapto-based silane coupling agents such as 3-mercaptopropyltrimethoxysilane, NXT-Z100, NXT-Z45, and NXT (3-octanoylthiopropyltriethoxysilane) manufactured by Momentive; vinyl-based silane coupling agents such as vinyltriethoxysilane and vinyltrimethoxysilane; 3-aminopropyltriethoxysilane, 3- Amino-based silane coupling agents such as aminopropyltrimethoxysilane and 3-(2-aminoethyl)aminopropyltriethoxysilane; glycidoxy-based silane coupling agents such as γ-glycidoxypropyltriethoxysilane and γ-glycidoxypropyltrimethoxysilane; nitro-based silane coupling agents such as 3-nitropropyltrimethoxysilane and 3-nitropropyltriethoxysilane; chlorine-based silane coupling agents such as 3-chloropropyltrimethoxysilane and 3-chloropropyltriethoxysilane, etc., preferably sulfide-based silane coupling agents and / or mercapto-based silane coupling agents, and particularly preferably mercapto-based silane coupling agents. These silane coupling agents may be used alone or in combination of two or more.
[0109] When a silane coupling agent is contained, from the perspective of cost performance, the content of the silane coupling agent (when multiple silane coupling agents are used in combination, the total amount of all silane coupling agents) is preferably less than 20 parts by mass, more preferably less than 15 parts by mass, further preferably less than 12 parts by mass, further preferably less than 9 parts by mass, and further preferably less than 7 parts by mass, relative to 100 parts by mass of silica. It should be noted that from the perspective of improving the dispersibility of silica, the content of the silane coupling agent is preferably greater than 1 part by mass, more preferably greater than 3 parts by mass, and further preferably greater than 5 parts by mass.
[0110] (Other compounding agents) In the rubber composition constituting the sidewall of the present invention, other compounding ingredients may include a plasticizer, wax, an antioxidant, stearic acid, zinc oxide, a vulcanizing agent, a vulcanization accelerator, and the like.
[0111] (Plasticizer) Plasticizer is a material that imparts plasticity to the rubber component, and is a concept that includes both plasticizers that are liquid (liquid) at room temperature (25°C) and plasticizers that are solid at room temperature (25°C). Examples of plasticizers include oils, liquid polymers, ester plasticizers, etc. in addition to resins. One type of plasticizer may be used alone, or two or more types may be used in combination.
[0112] Resin The rubber composition constituting the sidewall of the present invention may contain a resin. As the resin, petroleum resins, terpene resins, rosin resins, phenolic resins, etc. commonly used in the tire industry can be cited. These resin components can be used alone or in combination of two or more.
[0113] [Petroleum resin] Examples of the petroleum resin include C5-based petroleum resins, aromatic-based petroleum resins, and C5C9-based petroleum resins.
[0114] C5 petroleum resin refers to a resin obtained by polymerizing C5 fractions, which may be obtained by hydrogenating or modifying them. Examples of C5 fractions include petroleum fractions corresponding to 4 to 5 carbon atoms such as cyclopentadiene, pentene, pentadiene, and isoprene. As C5 petroleum resins, dicyclopentadiene resin (DCPD resin) is preferably used.
[0115] Aromatic petroleum resin refers to a resin obtained by polymerizing C9 fractions, which may be obtained by hydrogenating them or modifying them. As C9 fractions, for example, vinyl toluene, alkyl styrene, indene, methyl indene and other petroleum fractions equivalent to 8 to 10 carbon atoms can be cited. As specific examples of aromatic petroleum resins, for example, benzofuran indene resin, benzofuran resin, indene resin and aromatic vinyl resins are preferably used. As aromatic vinyl resins, for reasons of economy, easy processing and excellent heat generation, preferably a homopolymer of α-methylstyrene or styrene, or a copolymer of α-methylstyrene and styrene, more preferably a copolymer of α-methylstyrene and styrene. As aromatic vinyl resins, for example, commercial products of Clayton Company, Eastman Chemical Company, etc. can be used.
[0116] The C5C9-based petroleum resin refers to a resin obtained by copolymerizing the C5 fraction and the C9 fraction, and may be obtained by hydrogenating them or modifying them. The C5 fraction and the C9 fraction may include the above-mentioned petroleum fractions. As the C5C9-based petroleum resin, for example, commercial products of Tosoh Corporation, LUHUA Corporation, etc. may be used.
[0117] [Terpene resin] Examples of terpene resins include polyterpene resins formed from at least one of terpene compounds selected from α-pinene, β-pinene, limonene, dipentene, etc.; aromatic modified terpene resins using the above terpene compounds and aromatic compounds as raw materials; terpene phenol resins using terpene compounds and phenol compounds as raw materials; and resins obtained by hydrogenating these terpene resins (hydrogenated terpene resins). Examples of aromatic compounds that are raw materials for aromatic modified terpene resins include styrene, α-methylstyrene, vinyltoluene, divinyltoluene, etc. Examples of phenol compounds that are raw materials for terpene phenol resins include phenol, bisphenol A, cresol, xylenol, etc.
[0118] [Rosin-based resin] The rosin-based resin is not particularly limited, and examples thereof include natural resin rosin, and rosin-modified resins obtained by modifying the natural resin rosin by hydrogenation, disproportionation, dimerization, esterification, or the like.
[0119] [Phenolic resin] The phenolic resin is not particularly limited, and examples thereof include phenolic resins, alkylphenolic resins, alkylphenolacetylene resins, and oil-modified phenolic resins.
[0120] [Resin content] The content of the resin component is preferably greater than 1 part by mass, more preferably greater than 3 parts by mass, further preferably greater than 4 parts by mass, and further preferably greater than 5 parts by mass, relative to 100 parts by mass of the rubber component. In addition, the content of the resin component is preferably less than 30 parts by mass, more preferably less than 25 parts by mass, and further preferably less than 20 parts by mass.
[0121] "Oil" As oil, for example, process oil, vegetable oil, animal oil, etc. can be cited. As the above-mentioned process oil, paraffin process oil, cycloparaffin process oil, aromatic process oil, etc. can be cited. In addition, as an environmental measure, a process oil with a low content of polycyclic aromatic compounds (PCA) can also be used. As the above-mentioned low PCA content process oil, a mildly extracted solvate (MES), a treated distillate aromatic extract (TDAE: Treated Distillate Aromatic Extract), a heavy naphthenic oil, etc. can be cited. In addition, from the perspective of life cycle assessment, waste oil used in rubber mixers and engines, and waste cooking oil used in restaurants can be refined. One oil can be used alone, or two or more oils can be used in combination.
[0122] Liquid Polymer The liquid polymer is not particularly limited as long as it is a polymer in a liquid state at room temperature (25° C.), and examples thereof include liquid butadiene rubber (liquid BR), liquid styrene butadiene rubber (liquid SBR), liquid isoprene rubber (liquid IR), liquid styrene isoprene rubber (liquid SIR), liquid farnesene rubber, etc. The liquid polymer may be used alone or in combination of two or more.
[0123] 《Ester plasticizers》 As the ester plasticizer, for example, dibutyl adipate (DBA), diisobutyl adipate (DIBA), dioctyl adipate (DOA), di(2-ethylhexyl) azelate (DOZ), dibutyl sebacate (DBS), diisononyl adipate (DINA), diethyl phthalate (DEP), dioctyl phthalate (DOP), diundecyl phthalate (DUP), dibutyl phthalate (DBP), dioctyl sebacate (DOS), tributyl phosphate (TBP), trioctyl phosphate (TOP), triethyl phosphate (TEP), trimethyl phosphate (TMP), thymidine triphosphate (TTP), tricresyl phosphate (TCP), tri(xylene) phosphate (TXP), etc. The ester plasticizer can be used alone or in combination of two or more.
[0124] 《Content of plasticizers other than resins》 When a plasticizer other than the resin is contained, the content of the plasticizer other than the resin (when using multiple types, the total amount of all) is preferably greater than 1 part by mass, more preferably greater than 2 parts by mass, and further preferably greater than 3 parts by mass relative to 100 parts by mass of the rubber component. In addition, the content of the plasticizer is preferably less than 50 parts by mass, more preferably less than 40 parts by mass, and further preferably less than 30 parts by mass.
[0125] "wax" The wax is not particularly limited, and any wax commonly used in the tire industry can be appropriately used, for example, petroleum wax, mineral wax, synthetic wax, etc. can be mentioned. Among them, petroleum wax is preferred. As petroleum wax, for example, paraffin wax, microcrystalline wax, and their selected special waxes can be mentioned, among which paraffin wax is preferred. Waxes such as those manufactured and sold by Ouchi Shinko Chemical Industry Co., Ltd., Nippon Seira Co., Ltd., Paramelt Co., Ltd., etc. can be used. Waxes can be used alone or in combination of two or more.
[0126] When wax is contained, the wax content is preferably greater than 0.3 parts by mass, more preferably greater than 0.5 parts by mass, and further preferably greater than 1.0 parts by mass, relative to 100 parts by mass of the rubber component. On the other hand, the wax content is preferably less than 4.0 parts by mass, more preferably less than 3.0 parts by mass, and further preferably less than 2.0 parts by mass.
[0127] Anti-aging agent The antioxidant is not particularly limited, and any antioxidant commonly used in the tire industry can be appropriately used. As the antioxidant, for example, quinoline antioxidants, quinone antioxidants, phenol antioxidants, phenylenediamine antioxidants, metal carbamates, etc. can be cited. Among them, phenylenediamine antioxidants are preferred because they can better exert the effect of improving ozone resistance.
[0128] When an antioxidant is contained, the content of the antioxidant is preferably greater than 0.5 parts by mass, more preferably greater than 1.0 parts by mass, and further preferably greater than 2.0 parts by mass, relative to 100 parts by mass of the rubber component. On the other hand, the content is preferably less than 7.0 parts by mass, more preferably less than 6.0 parts by mass, and further preferably less than 5.0 parts by mass.
[0129] Stearic acid When stearic acid is contained, the content of stearic acid is preferably greater than 0.5 parts by mass, more preferably greater than 0.7 parts by mass, and further preferably greater than 1.0 parts by mass relative to 100 parts by mass of the rubber component from the viewpoint of processability. On the other hand, from the viewpoint of vulcanization speed, the content is preferably less than 10 parts by mass, more preferably less than 5 parts by mass, and further preferably less than 3 parts by mass.
[0130] Zinc Oxide When zinc oxide is contained, the content of zinc oxide is preferably greater than 0.5 parts by mass, more preferably greater than 0.7 parts by mass, and further preferably greater than 1 part by mass relative to 100 parts by mass of the rubber component from the viewpoint of processability. On the other hand, from the viewpoint of wear resistance, the content is preferably less than 10 parts by mass, more preferably less than 7 parts by mass, and further preferably less than 5 parts by mass.
[0131] 《Vulcanizing Agent》 The vulcanizing agent is not particularly limited, and a known vulcanizing agent can be used, for example, an organic peroxide, a sulfur-based vulcanizing agent, a resin vulcanizing agent, a metal oxide such as magnesium oxide, etc. can be cited. Among them, a sulfur-based vulcanizing agent is preferred. As the sulfur-based vulcanizing agent, for example, sulfur, a sulfur donor such as dimorpholine dithioate, etc. can be used. Among them, sulfur is preferably used. The vulcanizing agent can be used alone or in combination of two or more.
[0132] Sulfur includes powdered sulfur, precipitated sulfur, colloidal sulfur, surface-treated sulfur (oil-treated sulfur, special sulfur treated with a dispersant, masterbatch sulfur, etc.), insoluble sulfur (oil-treated insoluble sulfur, etc.), etc., and any of them can be used appropriately. Among them, powdered sulfur and insoluble sulfur are preferred. Sulfur can be, for example, sulfur manufactured and sold by Tsurumi Chemical Co., Ltd., Karuizawa Sulfur Co., Ltd., Shikoku Chemical Industry Co., Ltd., Flexsys Co., Ltd., Nippon Senryu Kogyo Co., Ltd., Hosoi Chemical Co., Ltd., etc.
[0133] When containing vulcanizing agent, relative to 100 parts by mass of rubber component, the content of vulcanizing agent is preferably greater than 0.4 parts by mass, more preferably greater than 0.7 parts by mass, further preferably more than 1.0 parts by mass, further preferably greater than 1.3 parts by mass. On the other hand, the content is preferably less than 6.0 parts by mass, more preferably less than 5.0 parts by mass, further preferably less than 3.0 parts by mass. When the content of vulcanizing agent is within the above range, there is a tendency to obtain a suitable reinforcement effect, and there is a tendency to better exert the effect of the present invention. It should be noted that when the vulcanizing agent such as oil-treated sulfur contains components other than sulfur, the content of the vulcanizing agent refers to the content of the sulfur component itself.
[0134] 《Vulcanization accelerator》 As the vulcanization accelerator, there is no particular limitation, and known vulcanization accelerators can be used, for example, sulfenamide, thiazole, thiuram, thiourea, guanidine, dithiocarbamic acid, aldehyde-amine or aldehyde-ammonia, imidazoline, or xanthate vulcanization accelerators can be cited. Among them, sulfenamide, thiuram, and guanidine are preferred, and sulfenamide is more preferred. The vulcanization accelerator can use, for example, a vulcanization accelerator manufactured and sold by Ouchi Shinko Chemical Industry Co., Ltd., Sanshin Chemical Industry Co., Ltd., etc. These vulcanization accelerators can be used in combination of one or more.
[0135] Examples of sulfenamide vulcanization accelerators include N-tert-butyl-2-benzothiazolyl sulfenamide (TBBS), N-cyclohexyl-2-benzothiazolyl sulfenamide (CBS), and N,N'-dicyclohexyl-2-benzothiazolyl sulfenamide (DZ). Examples of thiuram vulcanization accelerators include tetramethylthiuram monosulfide, tetramethylthiuram disulfide, and tetrabenzylthiuram disulfide (TBzTD). Examples of guanidine vulcanization accelerators include 1,3-diphenylguanidine (DPG), di-o-tolylguanidine, and o-tolylbiguanide.
[0136] The content of the vulcanization accelerator is preferably greater than 0.3 parts by mass, more preferably greater than 0.5 parts by mass, and further preferably greater than 0.6 parts by mass relative to 100 parts by mass of the rubber component. On the other hand, the content is preferably less than 8.0 parts by mass, more preferably less than 5.0 parts by mass, and further preferably less than 4.0 parts by mass. When the content of the vulcanization accelerator is within the above range, there is a tendency to ensure the breaking strength and elongation, and there is a tendency to better exert the effect of the present invention.
[0137] <Manufacturing> The rubber composition constituting the sidewall of the present invention can be produced by a known method, for example, by mixing the above-mentioned components using a rubber mixing device such as an open roll or a closed mixer (Banbury mixer, kneader, etc.).
[0138] The kneading process includes, for example, a basic kneading process of kneading compounding ingredients and additives other than a vulcanizing agent and a vulcanization accelerator, and a final kneading (F kneading) process of adding a vulcanizing agent and a vulcanization accelerator to the kneaded material obtained in the basic kneading process and kneading. In addition, the basic kneading process can also be divided into a plurality of processes as needed.
[0139] The kneading conditions are not particularly limited, and examples thereof include a method in which kneading is performed at a discharge temperature of 150 to 170° C. for 3 to 10 minutes in the basic kneading step and kneading is performed at 70 to 110° C. for 1 to 5 minutes in the final kneading step.
[0140] The tire of the present invention can be manufactured by a conventional method using the rubber composition. That is, the tire can be manufactured by the following method: using an extruder with a die of a predetermined shape, the unvulcanized rubber composition obtained by mixing the above-mentioned components into a rubber component as required is extruded into the shape of a tire sidewall, the unvulcanized tire sidewall thus obtained is bonded together with other tire components on a tire molding machine, and molded by a conventional method to form an unvulcanized tire, and the unvulcanized tire is heated and pressurized in a vulcanizer to manufacture the tire. The vulcanization conditions are not particularly limited, and for example, a method of vulcanizing at 150 to 200° C. for 10 to 30 minutes can be cited.
[0141] <Purpose> As tires, pneumatic tires, non-pneumatic tires, etc. can be cited. Among them, pneumatic tires are preferred. The tire can be used for passenger car tires, large passenger car tires, large SUV tires, trucks, buses and other heavy-duty tires, light truck tires, two-wheeled motor vehicle tires, racing tires (high-performance tires), etc. Among them, it can be appropriately used for passenger car tires. Here, passenger car tires refer to tires that are installed on a four-wheeled motor vehicle as a prerequisite, and the maximum load capacity WL is a tire of less than 1400kg. [Example]
[0142] The following are examples (embodiments) that are considered to be preferred when implemented, but the scope of the present invention is not limited to the examples. The tires obtained according to each table were studied using the various chemicals shown below, and the results were calculated based on the following evaluation method and are shown at the bottom of each table.
[0143] <Various Chemicals> The chemicals used in Examples and Comparative Examples are summarized and described below.
[0144] IR rubber: natural rubber (TSR20) BR: UBEPOL BR150B manufactured by Ube Industries, Ltd. (cis content 98% by mass, vinyl bond content 1% by mass) SBR: HPR840 manufactured by JSR Corporation (styrene content: 10.0% by mass, vinyl bond content: 42.0% by mol) CB (Carbon Black) 1: SHOWBLACK N550 (manufactured by Cabot Japan Co., Ltd., N2SA: 42m 2 / g, average primary particle size 48nm) CB (Carbon Black) 2: SHOWBLACK N660 (manufactured by Cabot Japan Co., Ltd., N2SA: 35m 2 / g, average primary particle size 80nm) rCB (regenerated carbon black): carbon black obtained by thermal decomposition of tires (ash content: 17% by mass) Silicon dioxide 1: ULTRASIL VN3 (N2SA: 175m 2 / g, average primary particle size: 17nm) Silicon dioxide 2: ULTRASIL 9100GR (N2SA: 235m 2 / g, average primary particle size: 15nm) Wax: Ozoace wax manufactured by Nippon Seiro Co., Ltd. Antioxidant 1: NOCRAC 6C (N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine) manufactured by Ouchi Shinko Chemical Industry Co., Ltd. Antioxidant 2: NOCRAC RD (poly(2,2,4-trimethyl-1,2-dihydroquinoline)) manufactured by Ouchi Shinko Chemical Co., Ltd. Oil: Diana process NH-70S (aromatic process oil) manufactured by Idemitsu Kosan Co., Ltd. Zinc oxide: Zinc Hua No. 1 manufactured by Mitsui Mining and Smelting Co., Ltd. Stearic acid: NOF Corporation's beaded stearic acid "Tsubaki" Sulfur: Seimi OT manufactured by Nippon Senryu Industry Co., Ltd. (containing 10% oil-insoluble sulfur) Vulcanization accelerator: Nocceler CZ (N-cyclohexyl-2-benzothiazolylsulfenamide (CBS)) manufactured by Ouchi Shinko Chemical Industry Co., Ltd.
[0145] <Production of Unvulcanized Rubber Composition> According to the formulations shown in Table 2-1 and Table 2-2 (collectively referred to as Table 2) and Table 3-1 and Table 3-2 (collectively referred to as Table 3), chemicals other than sulfur and a vulcanization accelerator were kneaded for 5 minutes using a 1.7 L closed Banbury mixer until the discharge temperature reached 170° C. to obtain a kneaded product. Subsequently, sulfur and a vulcanization accelerator were added to the obtained kneaded product using a twin-screw open mill, and kneaded for 4 minutes until the discharge temperature reached 105° C. to obtain an unvulcanized rubber composition.
[0146] <Manufacturing of Test Tires> According to Tables 2 and 3, the obtained unvulcanized rubber composition was extruded into the shape of a sidewall (SW) using an extruder with a die of a specified shape, and the unvulcanized sidewall thus obtained was bonded together with other tire components on a tire forming machine to form an unvulcanized tire, which was press-vulcanized at 170°C for 12 minutes to manufacture various test tires (Tire 1: 265 / 70R18, Tire 2: 205 / 55R16).
[0147] In addition, regarding the tiny ridges on the outer surface of the sidewall, during pressurized vulcanization, they are formed using a mold equipped with a side plate, and the side plate has an engraving for forming the tiny ridges on the opposite surface of the tiny ridge forming portion. The shapes of the tiny ridges A and B are as follows. It should be noted that the height h (mm) is the height of the tiny ridges at the maximum width position of the tire, the height h1 (mm) is the height of the tiny ridges at the radially outermost position of the tire, and the height h2 (mm) is the height of the tiny ridges at the radially innermost position of the tire. When the value of h1 is greater than h, the height of the tiny ridges gradually increases from the maximum width position of the tire to the radially outer side of the tire, and when the value of h2 is greater than h, the height of the tiny ridges gradually increases from the maximum width position of the tire to the radially inner side of the tire.
[0148] [Table 1] Table 1
[0149] <70℃tanδ、70℃E*> From the inner side of the sidewall of each test tire, a rubber test piece for viscoelasticity measurement with a length of 20 mm × a width of 4 mm × a thickness of 1 mm was cut out with the tire circumferential direction as the long side. For each rubber test piece, the EPLEXOR series manufactured by GABO was used to measure the loss tangent (70°C tanδ) and the complex elastic modulus (70°C E*) (MPa) in the elongation deformation mode under the conditions of measurement temperature: 70°C, initial strain: 10%, dynamic strain: ±1%, and frequency: 10 Hz.
[0150] <Crack resistance> The 265 / 70R18 test tire was mounted on a 18×8.5J rim, and the 205 / 55R16 test tire was mounted on a 16×6.5J rim. A drum (outer diameter: 1.7 m) was used to apply a load under the following conditions, and each test tire was driven continuously for 40,000 km, and the total length of the cracks in the sidewall generated after driving was calculated. Load: 4.74kN Internal pressure: 290kPa Speed: 100km / h
[0151] Based on the total length of the above cracks, the crack resistance index of the reference formulation was set to 100, and the crack resistance of each formulation was expressed by an index using the following calculation formula. A larger index indicates better crack resistance. (Crack resistance index) = (crack length of the reference formulation) / (crack length of each formulation) × 100
[0152] [Table 2-1]
[0153] [Table 2-2] Table 2-2 (Tire 1: 265 / 70R18)
[0154] [Table 3-1]
[0155] [Table 3-2] Table 3-2 (Tire 2: 205 / 55R16)
[0156] <Implementation Method> Preferred embodiments are described below.
[0157] [1] A tire, characterized in that the tire comprises a pair of sidewalls, The rubber composition constituting the sidewall contains a rubber component and silica, wherein the content of the silica is 20 parts by mass or more, preferably greater than 23 parts by mass, more preferably greater than 26 parts by mass, and further preferably greater than 29 parts by mass, relative to 100 parts by mass of the rubber component. When the loss tangent (tanδ) of the rubber composition at 70°C is 70°Ctanδ, the complex elastic modulus (MPa) of the rubber composition at 70°C is 70°CE*, and the thickness (mm) of the sidewall of the tire at the maximum width position is T, 70°Ctanδ, 70°CE* and T satisfy the following relationship: (1)70℃tanδ<0.0253×T+0.083, (2) 70℃E*≤10.0, Preferably, the difference obtained by subtracting the value on the left side from the value on the right side of formula (1) is greater than 0.010, more preferably greater than 0.020, further preferably greater than 0.030, further preferably greater than 0.040, further preferably greater than 0.050, further preferably greater than 0.060, and preferably, the right side of formula (2) is 8.0. [2] The tire according to [1], wherein the difference between the value on the left side and the value on the right side of equation (1) is greater than 0.070. [3] The tire according to [1] or [2], wherein the right side of formula (2) is 6.0, preferably 5.0, more preferably 4.7, further preferably 4.1, further preferably 4.0, further preferably 3.6. [4] The tire according to any one of [1] to [3], wherein The rubber composition contains carbon black, The content (in parts by mass) of the silica relative to 100 parts by mass of the rubber component is A SIL , the content (mass parts) of the carbon black is A CB When A SIL and A CB The following relations are satisfied: (3)A CB / A SIL ≤1, Preferably, the value of the right side of formula (3) is 0.90, more preferably 0.80, further preferably 0.70, further preferably 0.60, further preferably 0.50. [5] The tire according to any one of [1] to [4], wherein the rubber composition contains carbon black, and the carbon black contains regenerated carbon black. [6] The tire according to any one of [1] to [5], wherein the silica contains silica having an average primary particle size of 16 nm or less, preferably less than 16 nm, and more preferably 15 nm or less. [7] The tire according to any one of [1] to [6], wherein, when the tire weight (kg) of the tire is G and the maximum load capacity (kg) is WL, G and WL satisfy the following relationship: (4) G / WL≤0.0180, Preferably, the right side of formula (4) is 0.0170. [8] The tire according to [7], wherein the right side of equation (4) is 0.0165, preferably 0.0161. [9] The tire according to any one of [1] to [8], wherein at least one of the pair of sidewalls has a micro-ridge forming portion having a plurality of micro-ridges formed on an outer surface.
[10] The tire according to [9], wherein the micro-protrusions are in a columnar, conical, or rib-like shape.
[11] The tire according to [9] or
[10] , wherein the height of the micro-ridges is 0.03 mm to 0.50 mm, preferably 0.05 mm to 0.45 mm, more preferably 0.10 mm to 0.40 mm, and 20 or more micro-ridges are formed at intervals of 0.50 mm or less in at least one direction, and the micro-ridge forming portion has a 10 mm 2 The area above.
[12] A tire according to any one of [9] to
[11] , wherein the maximum width of the micro-ridges is greater than or equal to 0.03 mm and less than or equal to 5.00 mm, preferably greater than or equal to 0.05 mm and less than or equal to 3.00 mm, more preferably greater than or equal to 0.10 mm and less than or equal to 1.00 mm, and even more preferably greater than or equal to 0.10 mm and less than or equal to 0.50 mm.
[13] The tire according to any one of [9] to
[12] , wherein the height of the micro-ridges gradually increases from the maximum width position of the tire toward the outer side in the tire radial direction, and gradually increases from the maximum width position of the tire toward the inner side in the tire radial direction.
Claims
1. A tire, characterized in that: The tire includes a pair of sidewalls. The rubber composition constituting the sidewall contains a rubber component and silica, wherein the content of the silica is 20 parts by mass or more relative to 100 parts by mass of the rubber component. When the loss tangent tanδ of the rubber composition at 70°C is 70°Ctanδ, the complex elastic modulus of the rubber composition at 70°C is 70°CE*, and the thickness of the sidewall of the tire at the maximum width position is T, 70°Ctanδ, 70°CE* and T satisfy the following relationship: (1)70℃tanδ<0.0253×T+0.083, (2)70℃E*≤10.0, The unit of complex elastic modulus is MPa, and the unit of thickness is mm.
2. The tire according to claim 1, wherein: The difference between the value on the left side and the value on the right side of formula (1) is greater than 0.
070.
3. The tire according to claim 1, wherein: The right side of formula (2) is 6.
0.
4. The tire according to any one of claims 1 to 3, wherein The rubber composition contains carbon black, The content of the silica is A relative to 100 parts by mass of the rubber component. SIL , the content of the carbon black is A CB When A SIL and A CB The following relations are satisfied: (3)A CB / A SIL ≤1, The unit of the content of silica is part by mass, and the unit of the content of carbon black is part by mass.
5. The tire according to any one of claims 1 to 3, wherein The rubber composition contains carbon black, and the carbon black contains regenerated carbon black.
6. The tire according to any one of claims 1 to 3, wherein: The silicon dioxide contains silicon dioxide having an average primary particle size of 16 nm or less.
7. The tire according to any one of claims 1 to 3, wherein When the tire weight of the tire is G and the maximum load capacity is WL, G and WL satisfy the following relationship: (4) G / WL≤0.0180, The unit of tire weight is kg and the unit of maximum load capacity is kg.
8. The tire according to claim 7, wherein: The right side of formula (4) is 0.0165.
9. The tire according to claim 1, wherein: At least one of the pair of sidewalls has a micro-ridge forming portion having a plurality of micro-ridges formed on an outer surface.
10. The tire according to claim 9, wherein: The shape of the micro protrusion is columnar, frustum-shaped or rib-shaped.
11. The tire according to claim 9 or 10, wherein: The height of the micro-ridges is 0.03 mm or more and 0.50 mm or less, 20 or more micro-ridges are formed at intervals of 0.50 mm or less in at least one direction, and the micro-ridge forming portion has a 10 mm 2 The area above.
12. The tire according to claim 9 or 10, wherein: The maximum width of the microprotrusions is greater than or equal to 0.03 mm and less than or equal to 5.00 mm.
13. The tire according to claim 9 or 10, wherein: The height of the micro-ridges gradually increases from the maximum width position of the tire toward the outer side in the tire radial direction, and gradually increases from the maximum width position of the tire toward the inner side in the tire radial direction.
Citation Information
Patent Citations
Rubber composition for tire member, cap tread and sidewall, and pneumatic tire
JP2021014506A